Using smartphone apps for assessing Quality of Life - Work-InProgress Presentation - Estal-Muñoz, Víctor; Wingen, Tobias; Karakonstanti, Niki; Marenco, Pietro; Mareva, Silvana; Vintergaard Ott, Caroline; Schmidt, Barbara; Thomson, David; Kassianos, Angelos P. (My University, 2016)
Health-Related Quality of Life (HRQoL) is increasingly important in healthcare provision and is typically assessed using paper-and-pencil questionnaires. While HRQoL has predictive utility for clinical outcomes, the process of collecting, analyzing and storing paper-and-pencil data in clinical practice is effortful. Thus, more feasible measurement tools are needed. Employing an Ecologically Momentary Assessment (EMA) approach using smartphone applications can be a feasible and valid alternative for HRQoL assessment. Since EMA usually utilises electronic devices, it can reduce cost and labor and improve users’ motivation. Moreover, EMA allows collecting real-time experience and therefore has the potential to overcome a wide range of memory biases that compromise the validity of the HRQoL data. A smartphone application will be used to collect data with an adapted real-time version of the WHOQOL-BREF questionnaire. Over two weeks 420 participants from universities across Europe will report their real-time HRQoL, together with their current mood and activities. At the end of this period, participants will complete a retrospective assessment of their HRQoL, sleep quality and a feasibility questionnaire. The factorial structure, reliability and validity of real-time HRQoL will be compared with retrospective HRQoL responses. We expect the real-time HRQoL data to have adequate validity and reliability and positive responses on the feasibility questionnaire. This study will provide important novel insight into the efficacy of smartphone applications for HRQoL assessment. If shown to be valid, reliable and feasible, smartphone applications may have potential for facilitating HRQoL assessment, providing important information to clinicians and consequently improving health care provision.